Belgium : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Economic activity picked up in the course of 1999, despite the dioxin crisis of mid-year, owing to a recovery in export markets following the world financial turmoil of late 1998, supportive monetary policy in the euro area, improvements in business and consumer confidence, and continued growth in employment. The situation in labor markets remains unsatisfactory, with a high unemployment rate and a very slow participation rate. Executive Directors commended the Belgian authorities for the marked improvement in their fiscal situation in recent years.